Could vitamin D3 supplementation be used as a preventive strategy in genetically predisposed breast cancer: Existing evidence and future perspective - Amin, Mahnoor; Shabbir, Naqiha; Ali Muhammad, Soima (Journal of the Pakistan Medical Association, 2022)
This is a letter to editor and does not require an abstract.